Application Of Picture And Picture Learning Model To Improve Students’ Reading Through English Lessons - Anggraeni, Dian Nurvita (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This writing aims to improve the ability of students' interest in reading in elementaryschools through the learning model. Reading is one of the important things in all kinds oflearning process. Efforts to increase the reading interest of elementary school students area shared responsibility, between the students themselves, teachers and parents. The lowinterest in reading students in elementary schools is one of the obstacles, the lack of desireand willingness of the students themselves, the teacher also does not require students toread books when learning is taught to students. The results showed that with Picture andPicture learning activities became more interesting and students thought to furtherincrease their interest in reading. From the results of the analysis, it can increase thereading interest of elementary school students